Effectiveness of Educational Programme on Knowledge Regarding Hepatitis-B Prevention Among African Undergraduate Students of Health Sciences - Aikawa, Hussaini Muhammad (REAL in Nursing Journal, 2021)
Hepatitis B is an inflammatory disease of the liver which is caused by Hepatitis B Virus. It is a global problem, with 66% of all the population living in areas where there are high levels of infections. Hepatitis B infection may be due to lapses in the sterilization of instruments as well as improper waste management. Knowledge regarding Hepatitis B and safety precautions is needed to minimize the health care setting’s acquired infections among health personnel and students of health Science. The objectives of the study are: (a) To assess the knowledge regarding Hepatitis B prevention among African Students of Health Sciences (b) To evaluate the effectiveness of the structured teaching program regarding knowledge on prevention of hepatitis B among the students. A Quasi-experimental design was adopted and a sample of 50 African students were selected by non-probability purposive sampling technique. Data was collected by administering structured questionnaire before and after the implementation of structured teaching program. Data were analyzed using descriptive and inferential statistics and represented in tables and graphs. In the present study 66% of respondents had inadequate knowledge regarding Hepatitis B prevention before the implementation of structured teaching Program. But after the implementation of structured teaching program, 14% had moderate score and remaining 86% had adequate knowledge. The findings of the study revealed that the mean Post-test knowledge score (26.06) of the students exposed to structured teaching program was higher than the mean Pretest knowledge score (15.74) which was tested to be significant at P- value of 0.001 levels, which indicates the structured teaching program was effective. The overall findings of the study showed that there was a significant improvement in the knowledge scores after the administration of structured teaching program. Hence it can be concluded that structured teaching program was effective in improving the knowledge of African students regarding hepatitis B prevention.